Fiber Bragg Grating : bimetal temperature sensor for solar panel inverters / Mohd Afiq Ismail - Mohd Afiq , Ismail (2015)
This thesis demonstrates various techniques for generating passive Q-switched and soliton mode-locked fiber laser using Erbium-doped fiber and Thulium-Bismuth doped fiber laser as gain mediums. The techniques for obtaining Q-switched and soliton mode-locked fiber laser includes nonlinear polarization rotation (NPR), semiconductor saturable absorber and carbon-based saturable absorber; specifically, single-walled carbon nanotubes (SWCNT), graphene and non-conductive graphene oxide paper. A performance comparison is made between mode-locking using NPR technique and semiconductor saturable absorber. Based on the result, the semiconductor saturable absorber generates better quality of mode-locked pulse than using NPR. A single-walled carbon nanotubes (SWCNT) in a sodium dedocyl sulfate (SDS) solution is deposited onto a fiber ferrule using dripping technique. Due to the high insertion loss, a Q-switched pulse ensues. After adding a 200 meter single mode fiber (SMF) into the laser cavity, the pulse energy is high enough to saturate the SWCNT saturable absorber. Consequently, a strong soliton mode-locked pulse is generated. A simple and compact Q-switched fiber laser is demonstrated using graphene as saturable absorber. The saturable absorber is deposited onto a fiber ferrule by dripping a graphene solution and then is left to dry. A Q-switched pulse performances is compared between fiber lasers with one graphene saturable absorber and with two graphene saturable absorbers. A highly ordered pyrolitic graphite (HOPG) is mechanically exfoliated using a scotch tape. The resulting graphene is transferred onto a fiber ferrule and inspected using Raman spectroscopy. The transferred graphene has been identified as a single-layer. The ensuing pulsed fiber laser is a Q-switched, due to the large modulation depth of a single-layer graphene. A soliton mode-locked fiber laser is then generated by adding a 200 meter SMF. A soliton mode-locked is then demonstrated using Thulium-Bismuth doped fiber as gain medium. In the sixth experiment, a novel non-conductive graphene oxide paper is introduced as a saturable absorber. The resulting soliton mode-locked fiber laser has a time-bandwidth product (TBP) value of 0.315. The mode-locked fiber laser has a low mode-locking threshold but the pulse gradually destroys the paper. As a conclusion, this thesis shows the development of various techniques of generating Q-switched and mode-locked fiber, most notably using carbon based saturable absorber. This thesis also eases the focus on the saturable absorber, but instead, focusing on the cavity design to generate soliton mode-locked fiber lasers. Additionally, it introduces a non-conductive graphene oxide paper as a potential saturable absorber.